MIGRASI TENAGA KERJA INDONESIA ILEGAL DI MALAYSIA (STUDI KASUS DI KECAMATAN TEBING TINGGI KABUPATEN KEPULAUAN MERANTI) - Saputra, M. Azmi; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Meranti islansd is the regency with the highest poverty rate in Riau Province, by 27%. Besides, the limitations of basic infrastructure such as roads, electricity and clean water have also exacerbated this condition. Geographically, Meranti islands Regency is located on the eastern coast of Sumatra island, with a coastline bordering several neighboring countries and included in the Indonesia - Malaysia - Singapore (IMS-GT) Economic Growth Triangle (IMS-GT) area and has indirectly become Hinterland Free Trade Zone (FTZ) Batam-Tj Balai Karimun area. The administrative boundary of the Kepulauan Meranti Regency is the northern part bordering of Malacca Strait. This condition causes a large number of labor migration flows to Malaysia illegally. The research aims to find out the factors that make Indonesian Labor (TKI) from Meranti islands Regency migrate to Malaysia, also to find out the reasons why TKI prefer to work illegally rather than legally to improve their welfare. The research used a qualitative method by conducting observations, interviews and documentation on informants to obtain in-depth information regarding the problems in the study. The informants consisted of 5 people with different professions and one key informant, namely the Head of Department of Labor, Meranti islands Regency. The results showed that the motivating factors for people to work in Malaysia illegally are economic factors, family prestige, difficulty in finding employment opportunities, employment opportunities in Malaysia, proximity and cultural similarities between the Merant iislands  Regency and Malaysia. Keywords: TKI, Illegall, Meranti islands, Malaysia